Numerical and Experimental Investigation on the Attenuation of Electromagnetic Waves in Unmagnetized Plasmas Using Inductively Coupled Plasma Actuator - 林敏 徐浩军 魏小龙 梁华 宋慧敏 孙权 张艳华 (Plasma science & technology, 2015)
The attenuation of electromagnetic （EM） waves in unmagnetized plasma generated by an inductively coupled plasma （ICP） actuator has been investigated both theoretically and experimentally. A numerical study is conducted to investigate the propagation of EM waves in multilayer plasma structures which cover a square fiat plate. Experimentally, an ICP actuator with dimensions of 20 cm×20 cm×4 cm is designed to produce a steady plasma slab. The attenuation of EM waves in the plasma generated by the ICP actuator is measured by a reflectivity arch test method at incident waves of 2.3 GHz and 10.1 GHz, respectively. A contrastive analysis of calculated and measured results of these incident wave frequencies is presented, which suggests that the experiment accords well with our theory. As expected, the plasma slab generated by the ICP actuator can effectively attenuate the EM waves, which may have great potential application prospects in aircraft stealth.